Pengaruh Motivasi Kerja dan Beban Kerja Terhadap Kinerja Pegawai pada Kantor Kecamatan Polokarto Kabupaten Sukoharjo - Restu Susanto, Arga; Sutarno (Teewan Journal Solutions, 2025)
The State Civil Apparatus (ASN) is the frontline in carrying out government-based community services so that the resulting performance must be good and quality. The Polokarto District work unit, Sukoharjo Regency, is one of the agencies experiencing problems with decreased employee performance which in the pre-survey research is thought to be influenced by work motivation and workload. The purpose of this study was to analyse the significant effect of work motivation and workload on employee performance. The population in this study were 41 employees. The number of samples used was 33 ASNs who worked at the Polokarto District Office, Sukoharjo Regency using purposive sampling technique. The data collection technique used a questionnaire. The data analysis technique uses validity test, reliability test, classical assumption test, descriptive analysis, multiple linear regression analysis, t test, F test and coefficient of determination test. Hypothesis testing obtained that work motivation has a significant effect on employee performance at the Polokarto District Office, Sukoharjo Regency, while workload has no significant effect on employee performance at the Polokarto District Office, Sukoharjo Regency.